ANALISIS POTENSI SEKTOR UNGGULAN DAN PERUBAHAN STRUKTUR EKONOMI DI KABUPATEN SERANG PROVINSI BANTEN - Faujatul Hasanah; Iwan Setiawan; Trisna Insan Noor; Eka Purna Yudha (Universitas Galuh Ciamis, 2021)
Economic development is part of efforts to improve welfare. The rate of economic development in a region is indicated by the increasing GDP growth. The purpose of this research is to identify leading sectors and analyze the shift in economic structure in Serang Regency in the period 2015-2019. The analysis tools used are Location Quotient (LQ) and Shift Share (SS) analysis. The data used is secondary data obtained from the Central Statistics Agency of Serang Regency. The results showed that there are four sectors that have become the leading sectors in Serang Regency, namely agriculture, forestry, and fisheries; processing industry sector; government administration, defense, and social security sectors are mandatory; as well as the education services sector. Agriculture, forestry, and fisheries sector is the leading sector in Serang Regency with the largest LQ number of 1.56, but shift share analysis shows that this sector has slow growth and low competitiveness. The processing industry sector also has slow growth, but it is a leading sector and has high competitiveness. The structure of the economy in Serang regency has shifted towards the tertiary sector, it is characterized by an increasing percentage of tertiary sector contribution, while the secondary and primary sectors have decreased